Computational modelling of cell spreading and tissue regeneration in porous scaffolds. - Sengers, BG; Taylor, M; Please, C; Oreffo, R (2007)
Improved biological and mechanical functionality of musculoskeletal tissue-engineered constructs is required for clinical application, which can only be achieved by comprehensive multidisciplinary research. This review focuses on the contribution of computational modelling as a framework for obtaining an integrated understanding of key processes, which include: nutrient transport and utilization, matrix formation, cell population dynamics, cell attachment and migration, and local cell-cell interactions. Such an integrated perspective of these key aspects will be critical to open up new directions in tissue engineering research, as significant progress can be made by combining existing computational and experimental methods. Furthermore, theoretical modelling has enormous potential in applications ranging from the interpretation of experimental results and the identification of the main governing processes, to the optimization of practical tissue engineering protocols with implications therein for an increasing ageing population.